Dampak Undang-Undang Cipta Kerja (Omnibus Law) Terhadap Undang-Undang Administrasi Pemerintahan - Kasro, Edy; A, Koesrin Nawawie; Mardiyati, Siti (Universitas Muhammadiyah Palembang, 2022)
As a corrective step, it is appropriate that government administration issues be returned to their khitah. Regarding government administration, this needs to be implemented in the Job Creation Act. The goal is to create a bureaucratic culture that is fast, responsive, and responsible. The research method used in this article is normative with a statutory approach. This study seeks to reveal the impact of the omnibus law, whether it is in line with what is stipulated in the Government Administration Act. The results of the research article reveal that; First, the discretionary space of government officials must be limited on conditions that are in line with the provisions of the legislation. Second, the implementation of positive fictitious decisions must still involve the State Administrative Court.Keywords: Government Administration; Omnibus Law; Job Creation Law